Pendidikan Perempuan dan Pemisahan Kelas: Kajian Pemikiran Rahmah el-Yûnusiyah - Adib, M. Afiqul (At-Tafkir, 2022)
This article is a study on Women's Education and Class Segregation which is studied from the perspective of Rahmah el-Yûnusiyah This study aims to review one of the characteristics of the concept of education initiated by Rahmah el-Yûnusiyah, namely class separation. Rahmah believes that women need a separate education model that is separate from men because there are many issues about women that cannot be explained properly if there are men in one room. As a result, women do not understand deeply about themselves. This research is a literature study. Descriptive analysis is used in this study in order to get a complete picture and avoid subjective views. Data collection is carried out systematically according to existing procedures. The results obtained from this study reveal that class separation can be an option method that can be used so that the delivery of material about women can be explained more openly and in detail without feeling awkward because there is no opposite sex in one room. This will strengthen women's understanding of the material about women, namely about themselves, so that women can act, respond, and solve their own problems without any doubts in every action they take.